Ceria Nanoparticles Fabricated with 6‐Aminohexanoic Acid that Overcome Systemic Inflammatory Response Syndrome. Issue 9 (6th March 2019) - Jeong, Han‐Gil; Cha, Bong Geun; Kang, Dong‐Wan; Kim, Do Yeon; Yang, Wookjin; Ki, Seul‐Ki; Kim, Song I; Han, Juhee; Kim, Chi Kyung; Kim, Jaeyun; Lee, Seung‐Hoon
Abstract: Systemic inflammatory response syndrome (SIRS) is self‐destructive and uncontrollable inflammatory response of the whole body triggered by infection, trauma, or a variety of severe injuries. Although reactive oxygen species play a pivotal role in the development of SIRS, the trials with conventional antioxidants have failed to improve patient outcome. Ceria nanoparticles (CeNPs) have potent, autocatalytic reactive oxygen species scavenging activities, which may have sufficient therapeutic effects for SIRS. Herein, 3 nm CeNPs are fabricated totally in aqueous phase by using 6‐aminohexanoic acid (6‐AHA) and their Ce 3+ to Ce 4+ ratio is increased to enhance antioxidative properties. The obtained 6‐AHA‐CeNPs demonstrate strong antioxidative and anti‐inflammatory effects in various biofluids and inflammatory cells. In SIRS animal models, 6‐AHA‐CeNPs are demonstrated to reduce multiple organ injuries and inflammation. Moreover, 6‐AHA‐CeNPs decrease mortality and improve clinical scores of SIRS models. These findings suggest that 6‐AHA‐CeNPs have potential as a therapeutic nanomedicine for SIRS. Abstract : Systemic inflammatory response syndrome (SIRS) is a complex, self‐destructive process that occurs when the local control is lost and inflammation is overactivated throughout the body. Ceria nanoparticles (CeNPs) synthesized in aqueous phase using 6‐aminohexanoic acid (6‐AHA‐CeNPs) effectively treat remote organ injuries and improve survival rate in SIRS animal models.